2011
DOI: 10.1002/btpr.519
|View full text |Cite
|
Sign up to set email alerts
|

Screening for enzyme activity in turbid suspensions with scattered light

Abstract: New screening techniques for improved enzyme variants in turbid media are urgently required in many industries such as the detergent and food industry. Here, a new method is presented to measure enzyme activity in different types of substrate suspensions. This method allows a semiquantitative determination of protease activity using native protein substrates. Unlike conventional techniques for measurement of enzyme activity, the BioLector technology enables online monitoring of scattered light intensity and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…This assay is based on the BioLector technique, which allows the online monitoring of scattered light intensities in a continuously shaken microtiter plate [28,29]. In preliminary studies, it was shown that the BioLector technique can be applied in general for measuring enzymatic degradation of insoluble substrates [30]. However, this current study focused on proving the applicability of the BioLector technique for assaying, in particular, cellulase adsorption and activity.…”
Section: Research Articlementioning
confidence: 95%
“…This assay is based on the BioLector technique, which allows the online monitoring of scattered light intensities in a continuously shaken microtiter plate [28,29]. In preliminary studies, it was shown that the BioLector technique can be applied in general for measuring enzymatic degradation of insoluble substrates [30]. However, this current study focused on proving the applicability of the BioLector technique for assaying, in particular, cellulase adsorption and activity.…”
Section: Research Articlementioning
confidence: 95%
“…Microtiter plates containing 96 to 9,600 wells have been combined with colorimetric or fluorometric assays to screen for various enzyme properties. In a microtiter plate assay, the protein with its encoding DNA is compartmentalized in a single well; hence, enzymes with different activity profiles are easily distinguished and unable to diffuse or mix with other DNA–protein pairs. The substrates and products can be easily identified by macroscopic observation or measuring UV/vis absorbance or fluorescence through a plate reader (Figure ). Recently, a microbioreactor system named Biolector has been used to detect protease and cellulase activities. , Biolector enables online monitoring of the light scattering intensity and reduced nicotinamide adenine dinucleotide (NADH) fluorescence signals by adding light excitation and emission filters to the microtiter plate on a specially designed continuous shaking device.…”
Section: Methodologiesmentioning
confidence: 99%
“…286 Recently, a microbioreactor system named Biolector has been used to detect protease and cellulase activities. 284,285 Biolector enables online monitoring of the light scattering intensity and reduced nicotinamide adenine dinucleotide (NADH) fluorescence signals by adding light excitation and emission filters to the microtiter plate on a specially designed continuous shaking device. The scattered light signal difference between hydrolysis of an insoluble protein substrate and NADH-coupled enzyme indicates the protease and cellulase activity levels.…”
Section: Selection and Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 ] have combined the BioLector technology with a liquid handling system (RoboLector) to reduce the experimental efforts and increase the reproducibility. The Bio- and RoboLector platform have become widespread during the last years and is used in numerous biotechnological applications [ 2 , 12 15 ]. Besides the scattered light and biogenic fluorescences the dissolved oxygen tension (DOT) of the cultivation broth is another important process parameter.…”
Section: Introductionmentioning
confidence: 99%